Policies for Macrofinancial Stability : How to Deal with Credit Booms - Bakker, Bas.; Dell'Ariccia, Giovanni; Laeven, Luc.; Vandenbussche, Jerome (Washington, D.C. : International Monetary Fund, 2012)
This note explores the costs and benefits of different policy options to reduce the risks associated with credit booms, drawing upon several country experiences and the findings from econometric analysis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet